The Prediction of Hydrodynamic Performance of Pinisi Ship - Muhammad Akbar Asis; A Dian Eka Anggriani; Fadhil Rahmat Ramadhan (Department of Naval Architecture - Diponegoro University, 2023)
Pinisi ships are famous for their toughness across the ocean. The uniqueness of Pinisi is shipbuilding methods that are different without design engineering. The conditions present pinisi for tourist ships, problems have arisen recently, namely the number of Pinisi ship accidents. The main cause is bad water and technical factors. To improve safety and comfort, the aspect that needs to be studied hydrodynamic characteristics. The subject ship uses three samples of Pinisi ships produced by the Tanah Beru traditional shipyard. The hydrodynamic performance to be analyzed is hydrostatics, stability, resistance and ship motion, with several methods according to the respective standard to be analyzed. The shape of the pinisi hull is a rounded hull small coefficient block, and the largest change in hydrostatic parameters occurs at a draft of 0 meters to 0.25 meters. The resistance at a speed of 0-7 knots is relatively the same at every speed increase, but at speeds > 7 knots there is a change. RAO analysis for roll motion at a wave frequency of 1.5 – 1.75 rad/s for heading 90 degrees and for 45 degrees 3.65-3.80 rad/s. Heave motion occurs at a frequency of 4.25 rad/s – 4.4 rad/s with a wave direction of 0 degrees and a heading of 90 degrees smaller than the direction of the wave of 0 degrees. Evaluation of the stability arm, for variation KG critical, failed in 5/4H dan 1H in with B/T 3.43 to B/ T 5.00, while for the initial metacentric height parameter, all conditions still passed the criteria.